2020
DOI: 10.1111/1759-7714.13598
|View full text |Cite
|
Sign up to set email alerts
|

Identifying sarcopenia in advanced non‐small cell lung cancer patients using skeletal muscle CT radiomics and machine learning

Abstract: Background Sarcopenia has been confirmed as a poor prognostic indicator of lung cancer. However, the lack of abdominal computed tomography (CT) hindered the application to assess the status of sarcopenia. The purpose of this study was to assess the ability of chest CT radiomics combined with machine learning classifiers to identify sarcopenia in advanced non‐small cell lung cancer (NSCLC) patients. Methods This study retrospectively analyzed CT images of 99 patients with NSCLC. Skeletal muscle radiomics were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
0
22
0
2
Order By: Relevance
“…The data generated by software may be independent to the interobserver variability in sarcopenia quantification. Dong et al analysed CT images of 99 patients with advanced non-small cell lung cancer, with 40 of them having been identified as sarcopenic using skeletal muscle CSA at the L3 vertebral level; the authors extracted 854 radiomic and clinical features from the skeletal muscle area at the 12th thoracic vertebra level and five optimal features were selected [ 98 ]. An automated muscle measurement on a single-slice chest CT at T12 vertebral level was used by Lenchik et al to determine a relationship between muscle measurement with the rate of survival in a large patient population of 6.803 men and 4.558 women.…”
Section: The Role Of Artificial Intelligence (Ai) In Sarcopeniamentioning
confidence: 99%
“…The data generated by software may be independent to the interobserver variability in sarcopenia quantification. Dong et al analysed CT images of 99 patients with advanced non-small cell lung cancer, with 40 of them having been identified as sarcopenic using skeletal muscle CSA at the L3 vertebral level; the authors extracted 854 radiomic and clinical features from the skeletal muscle area at the 12th thoracic vertebra level and five optimal features were selected [ 98 ]. An automated muscle measurement on a single-slice chest CT at T12 vertebral level was used by Lenchik et al to determine a relationship between muscle measurement with the rate of survival in a large patient population of 6.803 men and 4.558 women.…”
Section: The Role Of Artificial Intelligence (Ai) In Sarcopeniamentioning
confidence: 99%
“…Missing values may cause confusion in model tting, and the output values are unreliable, and features with missing values exceeding 60% contain little availability information, so they are deleted directly. Because some features in the data have outliers, in order to avoid affecting the overall effect of the model, the remaining missing values are lled with median [10] .…”
Section: Discussionmentioning
confidence: 99%
“…It is also relevant to mention the use of Artificial Intelligence and radiomics in sarcopenia evaluation [82]. In particular, a recent study revealed that chest CT radiomics combined with machine learning classifiers allows to identify sarcopenia in advanced non-small cell lung cancer patients, by using skeletal muscle radiomics as a potential biomarker for sarcopenia identity [83]. The last application field that is worth mentioning is the gastrointestinal application.…”
Section: Radiomics In Clinical Practicementioning
confidence: 99%